2020
DOI: 10.1017/s1751731119003161
|View full text |Cite
|
Sign up to set email alerts
|

Review: Comparative methane production in mammalian herbivores

Abstract: Methane (CH4) production is a ubiquitous, apparently unavoidable side effect of fermentative fibre digestion by symbiotic microbiota in mammalian herbivores. Here, a data compilation is presented of in vivo CH4 measurements in individuals of 37 mammalian herbivore species fed forage-only diets, from the literature and from hitherto unpublished measurements. In contrast to previous claims, absolute CH4 emissions scaled linearly to DM intake, and CH4 yields (per DM or gross energy intake) did not vary significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 83 publications
4
33
1
1
Order By: Relevance
“…Several rodent hindgut fermenters and non-ruminant foregut fermenters also emit CH 4 of a magnitude as high as ruminants, but in contrast equids, macropods and rabbits produce much less (Clauss et al, 2020). There has been a move in recent years to understand why some domesticated ruminants produce lower CH 4 compared to others (Shi et al, 2014), and a subsequent push to utilize feed-based approaches to decrease ruminal methanogenesis (Jeyanathan et al, 2014).…”
Section: Role Of Anaerobic Fungi In Methanogenesismentioning
confidence: 99%
“…Several rodent hindgut fermenters and non-ruminant foregut fermenters also emit CH 4 of a magnitude as high as ruminants, but in contrast equids, macropods and rabbits produce much less (Clauss et al, 2020). There has been a move in recent years to understand why some domesticated ruminants produce lower CH 4 compared to others (Shi et al, 2014), and a subsequent push to utilize feed-based approaches to decrease ruminal methanogenesis (Jeyanathan et al, 2014).…”
Section: Role Of Anaerobic Fungi In Methanogenesismentioning
confidence: 99%
“…We estimate the fractionation factor ε between the carbon stable isotope composition of food resources ( 13 Cdiet) and enamel carbonate using a body mass-dependent equation calibrated for foregutfermenting mammals (Tejada-Lara et al, 2018; Table 1; see Text-SI and Appendix 1). While there is uncertainty in the optimal parameterization of ε (Clauss et al, 2020;Manthi et al, 2019) in our calculations this offset differs by less than 1.1 ‰ between taxa. In parallel to carbon isotope analysis of tooth enamel, for some individuals food remains stuck between cusps and teeth in the jaw were sampled also for carbon isotope analysis, if present, to directly assess the  13 C values of ingested plants (see Text-SI and Table S2).…”
Section: Enamel Carbon and Oxygen Stable Isotope Analysesmentioning
confidence: 77%
“…While previous work has indicated that host phylogeny influences archaeal abundance (1214, 30, 42), the work has largely been focused on methanogen diversity (especially Methanobrevibacter) and was strongly biased towards mammals. In this work, we not only identified a signal of host-Archaea phylosymbiosis while accounting for host diet, habitat, and other factors (Figure 2A), but we also identified specific archaeal ASVs to be associated with host phylogeny globally and for particular host clades (Figures 2C & S12), and we observed a significant signal of cophylogeny (Figure 2D & 2E).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, we provide evidence congruent with the hypothesis that Methanothermobacter abundance is modulated by host body temperatures. We note that among the host species in which methane emission data exists (14,30) , avian species with high abundances of Methanothermobacter have emission rates on the higher end of mammal emission rates ( Figure S20), suggesting that Methanothermobacter is indeed a persistent inhabitant in the gut of some avian species.…”
Section: Figure 2 Host Phylogeny and Diet Significantly Explain Diffmentioning
confidence: 99%